Gi2 proteins couple somatostatin receptors to low-conductance K+ channels in rat pancreatic alpha-cells. - Gromada, J; Høy, M; Olsen, H; Gotfredsen, C; Buschard, K; Rorsman, P; Bokvist, K (2001)
Somatostatin hyperpolarized rat pancreatic alpha-cells and inhibited spontaneous electrical activity by activating a low-conductance K+ channel (0.9 pS with physiological ionic gradients). This channel was insensitive to tolbutamide (a blocker of ATP-sensitive K+ channels) and apamin (an inhibitor of small-conductance Ca(2+)-activated K+ channels). Channel activation was prevented by pre-treating the cells with pertussis toxin, indicating the involvement of G-proteins. A direct interaction between an inhibitory G-protein and the somatostatin-activated K+ channel is suggested by the finding that intracellular application of guanosine 5'-O-(3-thiotriphosphate) (GTP gamma-S) and the G beta gamma subunit of G-proteins resulted in a transient stimulation of the current. Activation of the K+ current by somatostatin was inhibited by intracellular dialysis with specific antibodies to Gi1/2 and was not seen in cells treated with antisense oligonucleotides against G-proteins of the subtype Gi2. We conclude that somatostatin suppresses alpha-cell electrical activity by a Gi2-protein-dependent mechanism, which culminates in the activation of a sulphonylurea- and apamin-insensitive low-conductance K+ channel.